(untitled) (Al-Aasar, 2025)
Avni Doshi’s Burnt Sugar (2020) closely examines the painful and complicated relationship between mother and daughter. The main character is Tara, an emotionally distant, uncaring mother who is incapable of taking care of her daughter, Antara. This paper examines how Burnt Sugar redefines the concept of the Devouring Mother by applying trauma theory. It examines how the absence of a caring mother and the transmission of trauma influence Antara’s emotions while growing up. Applying concepts of Cathy Caruth (1996) and Bessel van der Kolk (2014), this research examines the psychological and emotional impact of having a neglectful mother, the trauma cycle, and how these influence how Doshi redefines the Devouring Mother concept. This paper presents a new perspective on mother-child relationships in contemporary literature. The research also examines the broader influence of generational trauma in family relationships and challenges society’s perception of motherhood.